Sustainable utilization of paper mill solid wastes via synthesis of nano silica for production of belite based clinker. (1st July 2019) - Vashistha, Prabhat; Singh, S.K.; Dutt, Dharm; Kumar, Vivek
Abstract: The industrial solid waste generation and its stockpile disposal have major environmental consequences. These consequences could be minimized through the solid waste application as a raw material in other industries. The current study focusses on the utilization of lime sludge with boiler ash synthesized nanosilica for production of belite based clinker at relatively lower temperature. Lime sludge was also used in combination with fly ash and boiler ash to check the synthesis of compounds at varying temperatures. Nanosilica was synthesized from pretreated boiler ash through alkali treatment and acid precipitation. The synthesized nanosilica has been characterized for specific surface area, crystallinity, surface functional groups and size. Three different mixtures, containing lime sludge with nanosilica, fly ash, and boiler ash are fired at temperatures ranging from 900 °C to 1200 °C and characterized for the synthesis of belite. Conventionally, belite is synthesized above 1200 °C, whereas the combined application of lime sludge and nanosilica reduces the temperature of belite synthesis to 900 °C without pre calcination or addition of any chemical stabilizer. In the case of lime sludge and boiler ash blend, belite formation takes place at the higher temperature (1100–1200 °C). Anorthite synthesis takes place in case of lime sludge and fly ash blend, due to high percentage of alumina present in fly ash. Lime sludge and nanosilica based belite clinker are used to develop newer cementitious binder. Hydration and strength properties of developed binder proved worthy as building materials. This study will present alternatives for sustainable utilization of lime sludge, fly ash and boiler ash in construction. Graphical abstract: Image 1079591 Highlights: Nano silica is synthesized from boiler ash. Lime sludge and Nanosilica are utilized for belite based clinker synthesis at low temperature. Blends of lime sludge with boiler ash and fly ash are also checked for clinker synthesis. The binder is prepared for the product development from synthesized belite clinker. This prepared binder is tested for hydration and strength properties and found sustainable.